Characterization of pore opening relevant residues in TM3 and TM4 domains of Orai1 - Andova, Ana-Marija (Jihočeská univerzita, 2022)
Calcium (Ca2+) ions play a crucial role in almost every aspect of cellular life. The most prominent calcium entry pathway into the cell is the calcium release-activated calcium (CRAC) channel, composed of the Orai1 protein, and the stromal interaction molecule STIM1. The channel is activated through conformational changes upon STIM1 coupling to the C-terminus of Orai1 protein following store depletion, which in turn allows Ca2+ influx into the cell. The abnormal function of the CRAC channel caused by mutations gives rise to distinct pathologies. Since it has not yet been elucidated how the signal propagation moves to the pore upon coupling, this thesis dives into its investigation by focusing on characterizing the TM3 and TM4 domains and their importance in leading to an open permissive conformation of the channel. The pivotal foundation for the creation of novel strategies in the modulation of the Orai1 function lies with the understanding of the dynamics of the Orai1 pore opening.
Characterization of pore opening relevant residues in TM3 and TM4 domains of Orai1
Keywords: ion channel; calcium signaling; CRAC channels; channel; CRAC; Orai1; Orai protein; STIM1; STIM protein; CRAC channel activation; molecular biology; electrophysiology; cell culture; mutation; TM domain; TM3; TM4; SOCE; pore opening; transmembrane domain; ion channel; calcium signaling; CRAC channels; channel; CRAC; Orai1; Orai protein; STIM1; STIM protein; CRAC channel activation; molecular biology; electrophysiology; cell culture; mutation; TM domain; TM3; TM4; SOCE; pore opening; transmembrane domain